A humanized murine model, demonstrating dominant progressive hearing loss caused by a novel KCNQ4 mutation (p.G228D) from a large Chinese family. Issue 2 (28th May 2022) - Cui, Chong; Zhang, Luping; Qian, Fuping; Chen, Yuxin; Huang, Bowei; Wang, Fang; Wang, Daqi; Lv, Jun; Wang, Xuechun; Yan, Zhiqiang; Guo, Luo; Li, Geng‐Lin; et al.
Abstract: The pathogenic variants in KCNQ4 cause DFNA2 nonsyndromic hearing loss. However, the understanding of genotype–phenotype correlations between KCNQ4 and hearing is limited. Here, we identified a novel KCNQ4 mutation p.G228D from a Chinese family, including heterozygotes characterized by high‐frequency hearing loss that is progressive across all frequencies and homozygotes with more severe hearing loss. We constructed a novel murine model with humanized homologous Kcnq4 mutation. The heterozygotes had mid‐frequency and high‐frequency hearing loss at 4 weeks, and moved toward all frequencies hearing loss at 12 weeks, while the homozygotes had severe‐to‐profound hearing loss at 8 weeks. The degeneration of outer hair cells (OHCs) was observed from basal to apical turn of cochlea. The reduced K + currents and depolarized resting potentials were revealed in OHCs. Remarkably, we observed the loss of inner hair cells (IHCs) in the region corresponding to the frequency above 32 kHz at 8–12 weeks. The results suggest the degeneration of OHCs and IHCs may contribute to high‐frequency hearing loss in DFNA2 over time. Our findings broaden the variants of KCNQ4 and provide a novel mouse model of progressive hearing loss, which contributes to an understanding of pathogenic mechanism and eventually treatment of DFNA2 progressive hearing loss. Abstract : This work identified a novel KCNQ4 pathogenic mutation KCNQ4: c.683G>A, p.G228D from a large Chinese family with DFNA2 nonsyndromic hearing loss. To recapitulate the DFNA2 patients, we generated a novel Kcnq4 G229D murine model, which contributes to an understanding of pathogenic mechanism and eventually treatment of DFNA2 progressive hearing loss.